Everyday classism in medical school: experiencing marginality and resistance - Beagan, Brenda L (Medical education, 2005)
Objective  To explore the medical school experiences of students who self‐identify as coming from a working‐class or impoverished family background. Methods  A questionnaire was administered to Year 3 medical students at a Canadian medical school and in‐depth interviews were held with 25 of these students (cohort 1). The same methods were repeated with another Year 3 class 3 years later (cohort 2). Results  While having (or not having) money was the most obvious impact of social class differences, students also discussed more subtle signs of class that made it easier or more difficult to fit in at medical school. Students from working‐class or impoverished backgrounds were significantly less likely to report that they fitted in well, and more likely to report that their class background had a negative impact in school. They were also more likely to indicate awareness that a patient's social class may affect their health care treatment. Conclusion  Students from working‐class or impoverished backgrounds may experience alienation in medical school. Through the commonplace interactions of ‘everyday classism’ they may experience marginalisation, isolation, disrespect and unintentional slights. At the same time, they suggest that their experiences of exclusion may strengthen their clinical practice.